A phase 1 study of the safety, pharmacokinetics and pharmacodynamics of escalating doses followed by dose expansion of the selective inhibitor of nuclear export (SINE) selinexor in Asian patients with advanced or metastatic malignancies. (March 2022) - Ho, Jingshan; Heong, Valerie; Peng Yong, Wei; Soo, Ross; Ean Chee, Cheng; Wong, Andrea; Sundar, Raghav; Liang Thian, Yee; Gopinathan, Anil; Yan Pang, Mei; Koe, Priscillia; Nathan Jeraj, Santhiay; et al.
Purpose: This phase 1 study aims to evaluate the tolerability and the recommended phase 2 dose of selinexor in Asian patients with advanced or metastatic malignancies. Experimental Design: A total of 105 patients with advanced malignancies were enrolled from two sites in Singapore (National University Hospital and the National Cancer Centre, Singapore) from 24 February 2014 to 14 January 2019. We investigated four dosing schedules of selinexor in a 3 + 3 dose escalation design with an additional Phase 1b expansion cohort. Adverse events were graded with the NCI Common Terminology Criteria for Adverse Events v 4.03. Pharmacodynamic assessments included nuclear cytoplasmic localization of p27, XPO1 cargo proteins pre and post selinexor dosing and pharmacokinetic assessments were conducted at doses between 40 and 60 mg/m 2 . Results: In our Asian patient cohort, dosing at 40 mg/m 2 given 2 out of 3 weeks, was the most tolerable for our patients. At this dose level, grade 3 adverse events included fatigue (8%), hyponatremia (23%), vomiting (5%), thrombocytopenia (5%), and anaemia (2%). Selinexor had a rapid oral absorption with median Tmax of 2 h and no PK accumulation after multiple doses of tested regimens. Complete responses were seen in two lymphoma patients. Partial responses were noted in three diffuse large B cell lymphomas, one Hodgkin's lymphoma and thymic carcinoma patient, respectively. Conclusion: Selinexor is tolerated by Asian patients at 40 mg/m 2 twice a week given 2 out of 3 weeks. A 1-week drug holiday was needed as our patients could not tolerate the current approved continuous dosing regimens because of persistent grade 3 fatigue, anorexia and hyponatremia.